Kiamat Dance: A Reflection of Local Wisdom in Kuripan Village, South Lampung, Indonesia - I Wayan Mustika (Institut Seni Indonesia Denpasar, 2024)
The Kiamat Dance is the closing dance of the ruwah or traditional wedding of the White Blood Queendom (Keratuan Darah Putih) for seven days and seven nights, known as nuhot. The Kiamat Dance, with its history rooted in the traditions of the White Blood Queendom, holds significant cultural and social value. As the closing dance of the ruwah, this dance symbolizes the culmination of the wedding festivities and marks the beginning of a new chapter in the lives of the newlyweds. The presence of this dance in various events beyond weddings highlights its versatility and adaptability, reflecting its enduring appeal and relevance in contemporary society. Through its rich symbolism and intricate movements, the Kiamat Dance embodies the core values and beliefs of the White Blood Queendom, serving as a testament to the community's cultural heritage and identity. This research aimed to describe the history, development, and local wisdom in the Kiamat Dance from Kuripan Village, South Lampung. This research employed a qualitative approach to produce descriptive data. The underlying theory used in this study was the behavioristic theory. Data collection techniques involved field observation, interviews, and documentation. The results showed that the art of the Kiamat Dance is the closing dance of the ruwah, a series of events for seven days and seven nights at the wedding in the White Blood Queendom. The Kiamat Dance is present on the last night as a closing dance. This dance was originally only found in the wedding ceremony of descendants of the White Blood Queendom. Still, almost every event has this dance nowadays, both in welcoming special guests and celebrating holidays. The values in this dance include religious, social, aesthetic, and educational values.